2014
DOI: 10.1111/jdv.12662
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid induced by m‐TOR inhibitors in renal transplant recipients

Abstract: The diagnosis of drug-induced events is crucial for early management, and particularly bullous eruptions affect patients' health and quality of life. Additional research is necessary to confirm the m-TOR inhibitors association, which exploit the possible mechanisms and eventually point out preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Mammalian target of rapamycin (mTOR) inhibitors (sirolimus, everolimus) has been implicated as a causative agent in two cases of BP in renal transplant recipients ( 88 ). BP has previously been described in renal transplant patients due to a graft-related cross reaction with the skin, or dysregulation of the immune system non-specifically inducing production of autoantibodies ( 42 , 89 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian target of rapamycin (mTOR) inhibitors (sirolimus, everolimus) has been implicated as a causative agent in two cases of BP in renal transplant recipients ( 88 ). BP has previously been described in renal transplant patients due to a graft-related cross reaction with the skin, or dysregulation of the immune system non-specifically inducing production of autoantibodies ( 42 , 89 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most sulfa-containing drugs (including furosemide & sulfamethoxazole), hydrochlorothiazide, nonsteroidal antiinflammatory drugs, lisinopril, captopril, and losartan have been implicated having associations with the development of BP. 22 The bullous dermatosis of hemodialysis, first described in 1975 by Barbara and Rowe, is characterized by blisters on sun-exposed parts of the scalp, face, arms, and the dorsum of the hand. 19 Quite on the contrary, mammalian target of rapamycin inhibitor (mTOR) inhibitor therapy has been specifically associated with BP lesions in renal transplant recipients, despite the IS properties of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…19 Quite on the contrary, mammalian target of rapamycin inhibitor (mTOR) inhibitor therapy has been specifically associated with BP lesions in renal transplant recipients, despite the IS properties of the drug. 22 The bullous dermatosis of hemodialysis, first described in 1975 by Barbara and Rowe, is characterized by blisters on sun-exposed parts of the scalp, face, arms, and the dorsum of the hand. 23 These skin lesions resemble those of porphyria cutanea tarda both clinically and histologically, and have been seen with chronic ambulatory peritoneal dialysis and chronic hemodialysis for years.…”
Section: Discussionmentioning
confidence: 99%
“…Id reactions can rarely be seen in the morphology of urticaria, follicules, papules, erythema multiforme, erythema annulare centrifugum, and erythema nodosum (10). Atzori et al presented a 37-year-old male patient with erythema multiforme-like Id reaction that developed on the distal portion of the extremity due to tinea infection on the nose (11). Castriota et al reported an erythema nodosum-like Id reaction in the lower extremity of a nine-year-old girl diagnosed with TP and stated that the clinical findings were relieved by antifungal therapy (12).…”
Section: Discussionmentioning
confidence: 99%